The Effectiveness of Rewards, Punishments, And Work Motivation on Employee Performance at Bank Mitra Syari'ah Gresik Regional Office - Maflakhah Ismiati; Wiwik Saidatur Rolianah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
In the midst of an increasingly competitive business environment, employee performance is a vital factor in achieving organizational goals. The performance of Bank Mitra Syariah employees has shown a decline over the past three years, prompting the implementation of an annual reward system alongside penalties such as salary deductions and performance evaluations. This study aims to examine the influence of rewards, punishments, and work motivation on employee performance at the Gresik Regional Office of Bank Mitra Syariah. Using a quantitative associative approach with a saturated sampling method, the research involved 65 employees as respondents. Data were collected through questionnaires and analyzed with multiple regression using SPSS version 29.0.2.0. The independent variables consist of Reward (X1), Punishment (X2), and Work Motivation (X3), while Employee Performance (Y) serves as the dependent variable. The findings are expected to contribute both theoretically, by enriching the human resource management literature in the Islamic banking context, and practically, by providing managerial insights for designing effective policies related to reward, punishment, and motivation systems in line with Sharia principles.